68PA novel anti-EGFR antibody HLX07 for potential treatment of squamous cell carcinoma of the head and neck. (24th November 2019) - Hou, M M; Ho, C L; Lin, H Y; Jiang, W; Liu, S; Hong, Y; Luk, A; Lin, S F; Hsieh, T C; Liu, E
Abstract: Background: HLX07 is a fully-humanised anti-epidermal growth factor receptor (EGFR) monoclonal antibody (mAb) with re-engineered Fab rendering its less immunogenic and better binding affinity than cetuximab. In-vivo studies of HLX07 demonstrated either equal or superior efficacy to cetuximab at the same dose level. Here, we present the data from the phase 1 study of HLX07 in advanced solid tumours. Methods: We conducted an open-label, dose-escalation study to evaluate the safety, maximum tolerated dose (MTD), PK and clinical response of HLX07 in subjects with recurrent or metastatic solid tumours unamendable to standard therapy. Subjects received once weekly intravenous infusion of HLX07 at doses of 50, 100, 200, 400, 600 and 800 mg until disease progression, withdrawal of consent or development of toxicities. Dose-limiting toxicities (DLTs) were evaluated within 28 days after the first dose and CT/MRI scans were evaluated every 8 weeks after the first infusion for treatment response. Safety, immunogenicity, PK and clinical response evaluations were performed throughout the study period. Results: HLX07 was first approved to initiate clinical trial by the Taiwan and US FDAs; subject recruitment began in late 2016. As of 13-June-2019, 19 subjects received HLX07 in the study with the longest follow-up period of over 224 days. Among the 16 subjects who had been evaluated for efficacy, 1 subject with advanced colon cancer in 600 mg cohort achieved partial response and 5 subjects in different cohorts achieved stable disease status. Particularly at the 400 mg dose level, 30% of patients were in stable disease status at week 16 evaluation. Possibly related to HLX07 AEs with grade >2 severity included skin rashes (10.6%), hypophosphatemia (5.3%), hypomagnesemia (5.3%) and hypocalcemia (5.3%). No novel safety signal was identified; no DLT was noted up to 800 mg cohort. The PK data up to 600 mg was described in the following table. Conclusions: HLX07 is generally well tolerated without reaching the MTD up to 800 mg weekly cohort and exhibits antitumour activity with durable objective responses at various doses. These findings support the initiation of a phase 1b/2 study of HLX07 plus chemotherapy in advanced solid tumours with the longest follow-up time of over 275 days as of 20-June-2019. Additionally, HLX07 is currently under safety and efficacy investigation combined with anti-PD-1 antibody, HLX10, in squamous cell carcinoma of head and neck. Clinical trial identification: HLX07-001 Phase 1 study (NCT02648490); HLX07-002 Phase 1b/2 study (NCT03577704). Legal entity responsible for the study: Shanghai Henlius Biotech, Inc.; Taiwan Henlix Biotech Co., Ltd. Funding: Shanghai Henlius Biotech, Inc. Disclosure: M.M. Hou: Research grant / Funding (institution): Taiwan Henlix Biotech Co., Ltd. C.L. Ho: Research grant / Funding (institution): Taiwan Henlix Biotech Co., Ltd. H.Y. Lin: Research grant / Funding (institution): Taiwan Henlix Biotech Co., Ltd. W. Jiang: Full / Part-time employment: Shanghai Henlius Biotech, Inc. S. Liu: Full / Part-time employment: Shanghai Henlius Biotech, Inc. Y. Hong: Full / Part-time employment: Shanghai Henlius Biotech, Inc. A. LUK: Full / Part-time employment: Shanghai Henlius Biotech, Inc. S.F. Lin: Full / Part-time employment: Taiwan Henlix Biotech Co., Ltd. T.C. Hsieh: Full / Part-time employment: Taiwan Henlix Biotech Co., Ltd. E. Liu: Full / Part-time employment: Taiwan Henlix Biotech Co., Ltd.